PENGARUH IKLIM KOMUNIKASI ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA ORGANISASI DI SUKU DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA ADMINISTRASI JAKARTA SELATAN - Memorianus Amazinhono (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2023)
Various complaints and problems arising from the services made by the Population and Civil Administration Office of South Jakarta, the performance of the organization is still not maximally seen in the non-conformity of the standard time of completion of the service that has been set. The research method used is survey method with regression and correlation analysis approach. Samples consisting of 102 respondents who have been determined. The result showed correlation between organizational communication climate with organizational performance obtained by R Square that is equal to 54,5% and the rest 45,5% contribution by other variable, correlation between job satisfaction to organizational performance obtained by R Square that is equal to 53,5% and the rest equal to 46.5% contribution by other variables, the correlation between the organizational communication climate and job satisfaction together to organizational performance obtained R Square that is equal to 72.8% and the rest of 27.2% contribution by other variables.